A Light‐Up Probe with Aggregation‐Induced Emission for Real‐Time Bio‐orthogonal Tumor Labeling and Image‐Guided Photodynamic Therapy. Issue 32 (18th July 2018) - Hu, Fang; Mao, Duo; Kenry,; Cai, Xiaolei; Wu, Wenbo; Kong, Deling; Liu, Bin
Abstract: Bio‐orthogonal tumor labeling is more effective in delivering imaging agents or drugs to a tumor site than active targeting strategy owing to covalent ligation. However, to date, tumor‐specific imaging through bio‐orthogonal labeling largely relies on body clearance to differentiate target from the intrinsic probe signal owing to the lack of light‐up probes for in vivo bio‐orthogonal labeling. Now the first light‐up probe based on a fluorogen with aggregation‐induced emission for in vivo bio‐orthogonal fluorescence turn‐on tumor labeling is presented. The probe has low background fluorescence in aqueous media, showing negligible non‐specific interaction with normal tissues. Once it reacts with azide groups introduced to tumor cells through metabolic engineering, the probe fluorescence is lightened up very quickly, enabling rapid tumor‐specific imaging. The photosensitizing ability was also used to realize effective image‐guided photodynamic tumor therapy. Abstract : Seeing the light : A bio‐orthogonal light‐up probe based on aggregation‐induced emission is designed to achieve rapid tumor‐specific turn‐on imaging and image‐guided photodynamic tumor therapy.